The effect of bitumen rheology to the permanent deformation of an asphalt concrete mixture - Muhamad Tarmidi, Mahvidayanti (2005)
Bitumen which functions as a binder in asphalt concrete mixture is also a visco-elastic and thermoplastic material. The characteristics are also influence by the temperature. It is because in hot condition or at high temperature, bitumen acts like a viscous liquid. In cold climate or at low temperature, bitumen behaves like an elastic solid. Even though bitumen is an elastic solid at low temperatures, it may become too brittle and crack when excessively loaded. However, the characteristic of an asphalt concrete are influenced by the rheology of bitumen which having two important properties; resistance to permanent deformation and fatigue. In this study, the most important thing to measure is the rheology of two different types of bitumen. The measurement was done using the Dynamic Shear Rheometer to obtain the viscoelastic properties of bitumen. The bitumen was then used in preparing an asphalt concrete mixture in order to test the rutting or permanent deformation using the Static Creep test. An analysis was done to verify the correlation between the rheology of two different types of bitumen and the rate of permanent deformation of the asphalt concrete mixture. Results obtained showed that both bitumens having a different rheology. Moreover, rutting parameter, G*/sin 8 could predict the different of creep performance. However, bitumen with identical value of G*/sin 5 at a different temperature would not necessarily produce mixture with the same creep compliance under the related temperature. Therefore, for further study it is recommended to focus on the load effect to the creep compliance.